2021
DOI: 10.1161/jaha.120.020425
|View full text |Cite
|
Sign up to set email alerts
|

Is Discordance Between Recommended and Actual Postacute Discharge Setting a Risk Factor for Readmission in Patients With Congestive Heart Failure?

Abstract: Background Readmissions in patients with congestive heart failure are common and often preventable. Limited data suggest that patients discharged to a less intensive postacute care setting than recommended are likely to readmit. We examined whether postacute setting discordance (discharge to a less intensive postacute setting than recommended by a physical and occupational therapist) was associated with hospital readmission in patients with congestive heart failure. We also assessed sociodemographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…A recent retrospective cohort study showed that patient non‐adherence to recommended post‐acute care was associated with an increased risk of readmission in patients with chronic HF, and this risk was not significantly increased in the less active population. 25 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent retrospective cohort study showed that patient non‐adherence to recommended post‐acute care was associated with an increased risk of readmission in patients with chronic HF, and this risk was not significantly increased in the less active population. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, for the patients themselves, any change in their personal compliance, mobility, and post‐discharge retreatment may significantly alter their prognosis. A recent retrospective cohort study showed that patient non‐adherence to recommended post‐acute care was associated with an increased risk of readmission in patients with chronic HF, and this risk was not significantly increased in the less active population 25 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations